Development of bead based multiplexed immunoassay for evaluation of midkine, syndecan-1, and ANGPTL4 in patient serum. Issue 1 (2nd January 2018) - Tarhoni, Imad; Fhied, Cristina L.; Pool, Mark; Liptay, Michael J.; Bonomi, Philip; Seder, Christopher W.; Borgia, Jeffrey A.
ABSTRACT: Background : Angiogenesis is associated with tumor progression in a range of malignancies. Herein, we develop custom immunobead assays for several mechanistically important targets and evaluated these against sera from cohorts of non-small cell lung cancer (NSCLC) patients. Methods : Antigen "capture" antibodies for midkine, syndecan-1, and ANGPTL4 were independently conjugated to MagPlex® Microspheres using standard carbodiimide/NHS-based chemistry. These reagents served as the basis for quantitative sandwich assay assembly using biotinylated detection antibodies and R-phycoerythrin-conjugated streptavidin reporter system. Standard curves were created using dilution series of recombinant target proteins with assay performance characteristics calculated, accordingly. Finally, we evaluated a range of serum samples from NSCLC patients ( n = 32) to verify assay performance. Results : Multiplexed assays for midkine, syndecan-1, and ANGPTL4 were developed with three orders of magnitude in dynamic range, excellent intra- and inter-assay precision, and accuracy parameters (<10%, and <15% variability, respectively). Detection and quantifications limits were suitable for the three assays to efficiently evaluate sera across a range of disease stages with a four-fold dilution factor. Conclusion : We successfully developed and analytically validated a 3-plex immunobead assay for quantifying midkine, syndecan-1, and ANGPTL4 in patient sera. This multiplexed assay will provide an important tool for future studies delineating the role of angiogenesis in lung cancer progression.